Penggunaan Arsip Lembaga Peradilan Umum di Indonesia Sebagai Sumber Sejarah - Prasadana, Muhammad Anggie Farizqi (Siginjai: Jurnal Sejarah, 2023)
The general judicial institutions in Indonesia comprise the District Court, High Court, and Supreme Court. These three entities adjudicate a spectrum of cases, spanning from general criminal and special criminal cases to special civil and religious civil cases, which are addressed at the courts of first instance, appeal, and cassation levels. The court proceedings encompass a plethora of information that is notably rich. Nevertheless, historians have not widely incorporated this resource into historical writing endeavors. This research endeavors to assess the extent to which archives from public justice institutions can be employed in historical documentation. Employing a literature study research method, the findings indicate that the diverse cases adjudicated by public justice institutions serve as invaluable historical sources. Their presence not only contributes information pertaining to the legal domain but also illuminates the social, economic, and political facets of a society. This wealth of information is encapsulated in the archives of proceedings, Investigation Reports (BAP), and court decisions. Access can be facilitated through the Supreme Court website or by directly visiting the court office.